Effects of Individualized Exercise Prescription vs. General Guidelines on Low-grade Inflammation and, Glucose and Lipid Metabolism in Overweight and Obese Subjects - Nyman, Jenny (My University, 2024)
Background and objective. This study investigates the impact of a three-month exercise prescription on inflammation markers, glucose and lipid profiles, and body composition among overweight and obese individuals. Additionally, it explores the effects of individualized versus general exercise guidelines and their influence on the parameters. Methods. In a randomized controlled trial, 89 participants aged 18-40 with a BMI over 27.5 were assigned to three intervention groups: Group 1 (n=14) adhered to standard exercise and nutrition guidelines, Group 2 (n=22) received a personalized intervention, and Group 3 (n=20) underwent a highly personalized intervention. Baseline and post-intervention assessments were conducted over a 12-week period, with additional follow-ups at 12 months. 56 participants attended the post-intervention measurements. Blood samples were analyzed for glucose, lipid profiles, and inflammatory markers, including CRP, TNF-α, and interleukins IL-1β, IL-6, IL-8, IL-10, IL-15, and IL-17A. Oxygen consumption (VO2) and exercise performance (W) at ventilatory thresholds (VT1 and VT2) and maximum capacity were measured during a step-incremental cycle-ergometer exercise test. Anthropometric values, encompassing weight (kg), Body Mass Index (BMI), Body Fat percentage (BF%), and Fat-Free Mass (FFM), were also assessed. Results. Significant negative changes were only observed in Group 3 for Weight, Body Fat Percentage, Visceral Fat, and BMI (p<0.05), with no significant changes in Group 1 and Group 2. All groups showed significant positive changes in power at both ventilatory thresholds (VT1 and VT2). Group 3 exhibited significant changes in all parameters. Significant differences between groups were observed in VO2max, VT1, and VT2. Changes in inflammatory marker levels, glucose profiles, or lipid profiles showed no statistically significant differences in all participants combined or among different groups. Significant positive correlations were found between anthropometric markers and VO2max, power, insulin, and HOMA-ir. Glucose and lipid profiles showed significant positive correlations with weight, visceral fat, and BMI, while no significant correlations were found in glucose profiles with cardiorespiratory and fitness markers. Of the lipid profiles, cholesterol and LDL correlated negatively with some cardiorespiratory and exercise performance markers, most notably VT1 and Power at VT1 and VT2. TNF- and IL-8 correlated significantly negatively with Weight, BMI, Fat %, and Visceral Fat. IL-8 also correlated with all power parameters and VO2max but not when scaled to Fat Free Mass. Conclusions. The study's findings support the efficacy of individualized exercise prescriptions in promoting favorable changes in health markers, offering insights for future interventions in obesity management. Consideration of the challenges in implementing highly individualized programs in broader populations is discussed, highlighting the need for innovative frameworks and tools for personalized exercise prescriptions.
Keywords: obesity, exercise intervention, randomized trial, physical activity, cytokines, myokines, low-grade inflammation, glucose profile, lipid profile, maximal oxygen uptake, anthropometry